he ETfforts to Reduce the Risk of Hypertension Complications in Prunggahan Wetan Village with the "CERMAT" Program - Wahyurianto, Yasin; Krisnawati, Ririn; Azuwin, Putri Riza; Ummah, Nadilla Shofiatul; Yanita, Happy April; Zahra, Jiesa Zayyina (Jurnal Pengabdian Masyarakat Bestari, 2024)
The number of hypertension sufferers in Prunggahan Wetan Village in 2022 will be 940 people, 840 of whom have received health services and 100 other people haven’t received. The aim of this activity is to provide health education about hypertension and healthy living behavior through the "CERMAT" program so that targets are able to implement it in an effort to reduce the risk of hypertension complications. The method used was lectures and demonstrations using PPT media, videos, and posters, the target number was 50 elderly people and was held over 3 meetings.  The result of this activity is that the majority of targets are able to implement the "CERMAT" program as an effort to reduce the risk of hypertension complications.